PEMBAHASAN KETUHANAN DALAM PUSTAKA BRAHMAVIDYA-UPANISAD HASIL TERJEMAHAN BEBERAPA SARJANA BARAT DAN TIMUR - I Ketut Donder (Pangkaja: Jurnal Agama Hindu, 2021)
Discourse about divinity in the Vedas is so extensive that it has produced many documents from reflection and in-depth study of the pursuit of God. This Brahmavidya-Upanisad is the centerpiece of the 39th Upanisad of 112 Upanisads translated by board scholars. This Brahmavidya-Upanisad is the result of contemplative research by ancient sages who used the paravidya-apaparavidya approach. This approach is a holistic approach, namely the paravidya approach is related to the investigation of the microcosm, and the aparavidya approach is related to the investigation of the macrocosm. The paravidya approach is a spiritual approach (subjective) and the aparavidya approach is a material approach (positive objective). The integration of this positivistic subjective-objective approach is a harmonious-integrative approach called a holistic approach, a blend of spirituality and science. The results of integrative contemplative research on the cOṁbination of spiritual-science found that the macrocosm and microcosm are the same but differ in intensity.The results of the research of these sages have given space for mankind to seek God within themselves or to seek God in all His creations that are in front of humans. There is nothing worse or better than man's search for God. If he is a layman then he can seek and place God outside of himself; but for spiritualists can worship God inside or outside themselves or both. This is a form of theology of freedOṁ and theology of liberation that can liberate humans frOṁ alienation frOṁ God.